Scorzonera sensu lato (Asteraceae, Cichorieae) – taxonomic reassessment in the light of new molecular phylogenetic and carpological analyses - Norbert Kilian; Maxim A. Zaika; Alexander P. Sukhorukov; Maya V. Nilova; Anna S. Speranskaya; Katy Jones; Anastasiya A. Krinitsina (Pensoft Publishers, 2021)
Scorzonera is a genus of perennial herbs and dwarf subshrubs widespread in the temperate and subtropical regions of Eurasia and N Africa. It comprises in its common wide sense some 180–190 species and is the largest and name-giving genus of the subtribe Scorzonerinae of the chicory tribe in the sunflower family (Asteraceae). Its circumscription has long been the subject of debate and available molecular phylogenetic analyses affirmed the polyphyly of Scorzonera in its wide sense. This paper presents a re-evaluation of Scorzonera and its related genera, based on carpological (including anatomical) and molecular phylogenetic analyses of a comprehensive sampling, for the first time spanning the entire subtribe and all major groups. Confirming the polyphyly of Scorzonera, this paper offers a revised classification of the subtribe, which recognises seven genera in accordance with the phylogenetic lineages resolved: Gelasia, Lipschitzia gen. nov., Pseudopodospermum, Pterachaenia, Ramaliella gen. nov., Scorzonera and Takhtajaniantha. A key to the revised genera and a characterisation of the genera and major clades are provided.